2013
DOI: 10.1039/c3cp50381j
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structures and magnetic properties of MoS2 nanostructures: atomic defects, nanoholes, nanodots and antidots

Abstract: Developing approaches to effectively induce and control the magnetic states is critical to the use of magnetic nanostructures in quantum information devices but is still challenging. Here MoS2-based nanostructures including atomic defects, nanoholes, nanodots and antidots are characterized with spin-polarized density functional theory. The S-vacancy defect is more likely to form than the Mo-vacancy defect due to the form of Mo-Mo metallic bonds. Among different shaped nanoholes and nanodots, triangle ones asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 75 publications
6
79
0
Order By: Relevance
“…Meanwhile, atomic vacancy defects in single-layer MoS 2 14,15 can be easily and even controllably obtained by chemical vapor deposition(CVD) 16 , field evaporation 17,18 and electron irradiation method 19 . However, reports have barely been found on magnetism appearing in MoS 2 with single vacancy 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, atomic vacancy defects in single-layer MoS 2 14,15 can be easily and even controllably obtained by chemical vapor deposition(CVD) 16 , field evaporation 17,18 and electron irradiation method 19 . However, reports have barely been found on magnetism appearing in MoS 2 with single vacancy 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the sulphur vacancy is the predominant point defect compared to Mo vacancy, regardless of the type of preparation method. 18 The effects of point defects on the electronic structure of LTMDs have also been theoretically studied by several groups using first principles calculations 16,17,[19][20][21][22][23][24][25] and 6-band tight-binding (TB) model 26 . Although, ab initio methods based on density functional theory (DFT) can achieve a good degree of accuracy to describe the electronic structure of pristine LTMD materials, they are limited in their application by the presence of defects in the samples.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 It has been found that the special triangular nanoflakes of TMDs exhibit many interesting physical and chemical properties. 24 This unique growth pattern inspires people to investigate the underlying reasons. Although density functional theory (DFT) based calculations 25 were carried out to understand the stability of triangular nanoflakes, the effect of edge configurations on the stability has not been studied yet.…”
mentioning
confidence: 99%
“…Therefore, the formation energy computed by DFT method in previous work 24 can be calculated now by the simple algebra equations in our Matrix method.…”
mentioning
confidence: 99%